1001 cars to dream of driving before you die - Heptinstall, Simon; Mason, Nick. (Sydney : New Holland, 2012)
It is almost impossible to imagine life today without one of the world-changing inventions of the twentieth century, the motor car. Appealing to car lovers ranging from vintage car spotters to armchair petrolheads, 1001 Cars to Dream of Driving Before You Die brings you the world's best cars.
Includes index.
Keywords: Automobiles; Automobiles -- Pictorial works